2018
DOI: 10.1016/j.pmrj.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Postneedling Soreness and Tenderness After Different Dosages of Dry Needling of an Active Myofascial Trigger Point in Patients With Neck Pain: A Randomized Controlled Trial

Abstract: NCT02190890 LEVEL OF EVIDENCE: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 46 publications
2
24
0
1
Order By: Relevance
“…It has been observed that performance of DN until no twitch response is evoked produces more post-needling soreness in comparison to when no twitch response is evoked. However, there seems to be no difference when few twitch responses are evoked in comparison to DN until no twitch response is evoked [49]. Therefore, DN with more twitch responses produces a greater mechanical stimulus, which could increase its therapeutic potential without increasing post-needling soreness.…”
Section: Pain and Disabilitymentioning
confidence: 99%
“…It has been observed that performance of DN until no twitch response is evoked produces more post-needling soreness in comparison to when no twitch response is evoked. However, there seems to be no difference when few twitch responses are evoked in comparison to DN until no twitch response is evoked [49]. Therefore, DN with more twitch responses produces a greater mechanical stimulus, which could increase its therapeutic potential without increasing post-needling soreness.…”
Section: Pain and Disabilitymentioning
confidence: 99%
“…14,15 MTrPs aktif dianggap ada jika tiga dari empat kriteria tersebut ada. 16,17 Kriteria lain yang merupakan konfirmasi MTrPs antara lain adanya local twitch response (LTR) yang muncul saat dilihat atau diraba. LTR diinduksi oleh penetrasi jarum pada titik nyeri.…”
Section: Pembahasan Nyeri Miofasial Servikalunclassified
“…Postneedling soreness is thought to be result of neuromuscular injury, and hemorrhage and inflammatory reaction caused by the needle. The needle insertions, pain perceived during treatment (Martin-Pintado-Zugasti et al, 2018;Martin-Pintado-Zugasti et al, 2016) and psychosocial factors (Martin-Pintado-Zugasti et al, 2017) have been shown to correlate with postneedling soreness. Postneedling soreness is usually resolved within 72 hours and commonly within clinical practice patients receiving DN do not consider this soreness relevant.…”
Section: Gaubeca-gilarranzmentioning
confidence: 99%